The Role of Proteoglycans in Cancer Metastasis and Circulating Tumor Cell Analysis - Ahrens, Theresa D.; Bang-Christensen, Sara R.; Jørgensen, Amalie M.; Løppke, Caroline; Spliid, Charlotte B.; Sand, Nicolai T.; Clausen, Thomas M.; Salanti, Ali; Agerbæk, Mette Ø. (Frontiers in Cell and Developmental Biology, 2020)
Circulating tumor cells (CTCs) are accessible by liquid biopsies via an easy blood draw. They represent not only the primary tumor site, but also potential metastatic lesions, and could thus be an attractive supplement for cancer diagnostics. However, the analysis of rare CTCs in billions of normal blood cells is still technically challenging and novel specific CTC markers are needed. The formation of metastasis is a complex process supported by numerous molecular alterations, and thus novel CTC markers might be found by focusing on this process. One example of this is specific changes in the cancer cell glycocalyx, which is a network on the cell surface composed of carbohydrate structures. Proteoglycans are important glycocalyx components and consist of a protein core and covalently attached long glycosaminoglycan chains. A few CTC assays have already utilized proteoglycans for both enrichment and analysis of CTCs. However, the biological function of proteoglycans on clinical CTCs has not been studied in detail so far. Therefore, the present review describes proteoglycan functions during the metastatic cascade to highlight their importance to CTCs. We also outline current approaches for CTC assays based on targeting proteoglycans by their protein cores or their glycosaminoglycan chains. Lastly, we briefly discuss important technical aspects, which should be considered for studying proteoglycans.